2022
DOI: 10.3390/ani12223219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Compound Probiotics on Growth Performance, Serum Biochemical and Immune Indices, Antioxidant Capacity, and Intestinal Tissue Morphology of Shaoxing Duck

Abstract: This experiment was conducted to investigate the effects of compound probiotics on growth performance, serum biochemical and immune indices, antioxidant capacity, and the intestinal tissue morphology of Shaoxing ducks. A total of 640 1-day-old healthy Shaoxing ducks of similar body weight were randomly divided into two treatment groups with eight replicates each and forty ducks per replicate. The ducks were fed a basal diet (Ctrl) or a basal diet supplemented with 0.15% compound probiotics (CP) for 125 d. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Previous studies have demonstrated that the administration of probiotics to ducks can lead to an augmentation in the activity of digestive enzymes inside the small intestine (Khattab et al, 2021). This, in turn, contributes to the enhancement of digestive system functionality and an increase in the digestibility of feed (Sun et al, 2022;Siti et al, 2023). According to Khattab et al (2021), the inclusion of probiotics in the diet of ducks resulted in the increased activity of digestive enzymes, including amylase, lipase, and protease, within their small intestines, as compared to those not administered with probiotics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that the administration of probiotics to ducks can lead to an augmentation in the activity of digestive enzymes inside the small intestine (Khattab et al, 2021). This, in turn, contributes to the enhancement of digestive system functionality and an increase in the digestibility of feed (Sun et al, 2022;Siti et al, 2023). According to Khattab et al (2021), the inclusion of probiotics in the diet of ducks resulted in the increased activity of digestive enzymes, including amylase, lipase, and protease, within their small intestines, as compared to those not administered with probiotics.…”
Section: Resultsmentioning
confidence: 99%
“…It secretes exogenous digestive enzymes (Abd El-Moneim and Sabic, 2019), which can improve nutrient digestion. Also, it can improve health, performance, ration efficiency, and it can ameliorate the intestinal morphology of ducks (Guo et al, 2016;Zurmiati et al, 2017b;Li et al, 2022;Sun et al, 2022). However, to date there have been no reports concerning the response of male Bayang duck supplemented with a probiotic Bacillus subtilis FNCC 0059.…”
Section: Introductionmentioning
confidence: 99%
“…Clostridium butyricum and Enterococcus faecalis enhanced the intestinal barrier integrity and improved the intestinal immune function in lipopolysaccharide-challenged piglets ( Wang et al., 2019 ). C. butyricum, Bacillus subtilis, and B. licheniformis also improved the growth performance and intestinal morphology in chickens, ducks, and cows ( Sun et al., 2022 ; Wang et al., 2017 , 2023 ; Xing et al., 2015 ). Moreover, dietary L-Trp supplementation significantly increased the levels of total antioxidant capacity (T-AOC), glutathione peroxidase (GSH-Px), and catalase (CAT) in the serum and stocking density in white pekin ducks ( Liu et al., 2015 ).…”
Section: Trp Nutrition In Diseases Preventionmentioning
confidence: 92%
“…2 ). Despite that the KP is mainly activated in the host cells, recent studies found that a few bacterial species like Burkholderia cepacia J2315 and Pseudomonas fluorescens strain KU-7 also activate the KP ( Hasegawa et al., 2000 ; Sun et al., 2022 ). B. cepacia J2315 metabolizes L-Trp into 2-amino-3-carboxymuconate semialdehyde, which is further degraded to pyruvate and acetate ( Colabroy and Begley, 2005 ).…”
Section: Origin and Metabolic Outcomes Of Dietary Trpmentioning
confidence: 99%
“…Duck farming, another economically significant aspect of Bangladesh's poultry industry, has also seen a shift towards probiotic inclusion in feed. Studies reveal that 0.2 g per kilogram of diet from a blend of Lactobacillus acidophilus and Lactobacillus casei lead to notable changes in the blood's biochemical profile, improvements in egg composition, and the establishment of a stable gut microbiota ( Khattab et al, 2021 ; Sun et al, 2022 ). These outcomes contribute to enhanced growth performance and a reduction in the incidence of diseases, reinforcing the potential of probiotics in promoting the health and productivity of ducks ( Li et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%